Survey on Parking Satisfaction at Universiti Tun Hussein Onn Malaysia Campus - Muhammad Syazwi Shafie, (Recent Trends in Civil Engineering and Built Environment, 2020)
Use of the transportation system in university is a major pulse in the daily activities for students and university staff. This is because by having a good traffic system allows traveling plans effectively. Rapid progress in the production of vehicles provides opportunities for students, especially to have their own vehicle. For this study, the scope of research done is focused on areas of campus parking on Tun Hussein Onn University involving a total of fourteen thousand students  and three thousand staff. Although the road networking is designed effectively but the parking problems continuing to occur. As a result the students and staff dissatisfaction with the parking space of Tun Hussein Onn University, especially in the main buildings. The university authorities have attempted to solve the parking problem. Thus a parking feasibility study should be carried out and questionnaire session will be conducted to determine the suitability of parking. The data analysis is also made to identify the actual rate parking demand compared with the provision of those now. Overall, the available parking areas at Tun Hussein Onn University experiencing a shortage of parking spaces. Survey results will be used to identify problems parking and also identify the attitude of the consumer.